MICROBIAL DECOLOURIZATION OF DISTILLERY SPENT WASH BY PSEUDOMONAS STUTZERI ABS009 - ABHIJIT B. SHINDE; SANDIP S. GARE (The Bioscan, 2025)
Cane molasses-based distilleries are major contributors to water pollution due to their discharge of dark brown coloured waste water having high values of chemical oxygen demand (COD) and biological oxygen demand (BOD). Improper disposal contaminates aquatic and terrestrial ecosystems, necessitating effective pretreatment methods. In this study, a bacterial strain Pseudomonas stutzeri ABS009 was used to decolourize distillery spent wash. The decolourization process was evaluated under varying environmental conditions and with different nutritional parameters. Maximum decolourization (38.90%) was achieved at 35°C after 6 days of incubation under static conditions with 1.25 % glucose (w/v) and 0.3% peptone (w/v) at pH 6.0. A seed germination test using Phaseolus mungo L. showed a notable decrease in the toxicity of the spent wash that had been treated with bacterial strain. These findings contribute to the development of an eco-friendly, cost-effective, and socially acceptable method for treating distillery spent wash.